A comparative analysis of engineering and economical suitability of bituminous mastics containing waste fillers. (December 2022) - Choudhary, Jayvant; Sukhija, Mayank; Gupta, Ankit
Abstract: This novel study focused on comparing the effect of waste glass powder (GP), waste-dried Kota stone slurry (KS), glass-hydrated lime composite (GL), and conventional stone dust (SD) fillers on the engineering and economical performance of bituminous mastics. Bituminous concrete mixes incorporating the fillers mentioned above at multiple proportions (4%, 5.5%, 7.0%, and 8.5% by weight) were prepared and characterized. The filler-bitumen ratio corresponding to each bituminous mix was determined and used to design its corresponding bituminous mastic. The rheological characteristics of bituminous mastics were compared by investigating their engineering performance against rutting, fatigue, and long-term ageing, using a series of sophisticated tests, namely multiple stress creep and recovery (MSCR), linear amplitude sweep (LAS), and ageing index (AI) analysis, respectively. It is inferred that an increase in filler volume concentration in the bituminous mastics leads to its enhancement in resistance against rutting and long-term ageing. More specifically, GL mastics outperformed in terms of rutting and ageing resistance, followed by GP, KS, and SD mastics. Considering fatigue resistance, SD mastics indicated higher fatigue life than the mastics prepared with waste fillers. In terms of economic performance, using a higher amount of fillers in mastics tends to reduce the cost-benefit ratio (C/B). In particular, utilizing GL mastic seems to deliver better engineering performance in a more economical manner, followed by GP, KS, and SD. These inferences were further validated using statistical analysis, confirming the significant influence of filler type and filler content over the analyzed engineering parameters.